Compositional Current - Voltage Power Converters: Schematics and Function - Petrauskas, G.; Leonavicius, V. (Elektronika ir Elektrotechnika, 1998)
Power converters with higher frequency component used in energy transmission from Renewable energy sources to electrical grid are discussed. Properties and operation are presented. Single phase and 3-phase system schematics are presented.